2020
DOI: 10.1093/socrel/sraa025
|View full text |Cite
|
Sign up to set email alerts
|

Moral Religiosities: How Morality Structures Religious Understandings during the Transition to Adulthood

Abstract: Religiosity remains an important sociological concept, from assessing religion’s effects on various outcomes to describing large-scale religious change. And yet conceptualizing religiosity—as a measure of intensity of religious practice—requires accounting for how respondents understand religious practice. Drawing on four waves of longitudinal interview data from the National Study of Youth and Religion (NSYR), this paper examines the religious understandings of young Americans as they develop over 10 years. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Existing research confirms the relationship between religious traits and moral ones, showing more religiously committed people to have higher levels of the binding moral foundations as well as values related to tradition, conservation, and conformity (Graham and Haidt 2010;Schwartz and Huismans 1995). We should thus expect a close, dynamic relationship between the religious domain of experience and the development of moral beliefs and sensibilities (Rotolo 2021).…”
Section: Religion and Moral Characteristicsmentioning
confidence: 80%
See 4 more Smart Citations
“…Existing research confirms the relationship between religious traits and moral ones, showing more religiously committed people to have higher levels of the binding moral foundations as well as values related to tradition, conservation, and conformity (Graham and Haidt 2010;Schwartz and Huismans 1995). We should thus expect a close, dynamic relationship between the religious domain of experience and the development of moral beliefs and sensibilities (Rotolo 2021).…”
Section: Religion and Moral Characteristicsmentioning
confidence: 80%
“…Social scientific research, popular perception, and intuitive understanding all support the proposition of a strong link between religion and morality (e.g., Rotolo 2021;Smith, Ritz, and Rotolo 2019). Work applying conceptualizations of morality from social psychology, namely, moral foundations and values (Graham et al 2011;Schwartz 1992), has shown religious identification, belief, and behavior to relate to binding and communally oriented moral boundaries and ends (Graham and Haidt 2010;Schwadel and Hardy 2022).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations